Primitive model electrolytes. A comparison of the HNC approximation for the activity coefficient with Monte Carlo data - Gutiérrez-Valladares, E.; Lukšič, M.; Millán-Malo, B.; Hribar-Lee, B.; Vlachy, V. (Condensed Matter Physics, 2011)
Accuracy of the mean activity coefficient expression (Hansen-Vieillefosse-Belloni equation), valid within the hypernetted chain (HNC) approximation, was tested in a wide concentration range against new Monte Carlo (MC) data for +1:-1 and +2:-2 primitive model electrolytes. The expression has an advantage that the excess chemical potential can be obtained directly, without invoking the time consuming Gibbs-Duhem calculation. We found the HNC results for the mean activity coefficient to be in good agreement with the machine calculations performed for the same model. In addition, the thermodynamic consistency of the HNC approximation was tested. The mean activity coefficients, calculated via the Gibbs-Duhem equation, seem to follow the MC data slightly better than the Hansen-Vieillefosse-Belloni expression. For completeness of the calculation, the HNC excess internal energies and osmotic coefficients are also presented. These results are compared with the calculations based on other theories commonly used to describe electrolyte solutions, such as the mean spherical approximation, Pitzer's extension of the Debye-Hückel theory, and the Debye-Hückel limiting law. Точнiсть виразу для коефiцiєнта середньої активностi (рiвняння Гансена-Вiллефосса-Беллонi), справедливого у гiперланцюговому (ГЛ) наближеннi, перевiрялася у широкому iнтервал i концентрацiї вiдносно нових даних Монте-Карло (МК) для примiтивних моделей електролiту +1:−1 i +2:−2. Вираз мiстить ту перевагу,що надлишковий хiмiчний потенцiал можна отримати прямо, не вдаючись до трудомiсткого розрахунку Гiббса-Дюгема. Ми виявили, що результати ГЛ наближення для коефiцiєнта середньої активностi добре узгоджуються з проведеними для такої самої моделi числовими розрахунками. Крiм того, було протестовано термодинамiчну узгодженiсть ГЛ наближення. Виглядає так, що коефiцiєнти середньої активностi, порахованiза допомогою рiвняння Гiббса-Дюгема, узгоджуються з даними Монте-
Карло трохи краще нiж вираз Гансена-Вiллефосса-Беллонi. Для цiлiсностi розрахунку представлено також ГЛ надлишковi внутрiшнi енергiї та осмотичнi коефiцiєнти. Цi результати порiвнюються з розрахунками на основi iнших загальновiдомих теорiй, якi описують розчини електролiтiв, зокрема зi середньо-сферичним наближенням, модифiкацiєю Пiтцера теорiї Дебая-Гюккеля, i граничним законом Дебая-Гюккеля.